PARENTAL EMOTIONAL VALIDATION, SOCIAL SUPPORT, AND MENTAL RESILIENCE AMONG VOCATIONAL HIGH SCHOOL STUDENTS FROM INTACT FAMILIES - Diajeng Nurul Fatihah; Abdullah Pandang; Muhammad Amirullah; Muhammad Fiqri Syahril (CV. TOTUS TUUS, 2026)
Vocational high school students experience developmental demands related to academic achievement, social adjustment, and preparation for work. Although students from intact families are often assumed to receive adequate emotional protection, structural family completeness does not always guarantee emotional validation or sufficient social resources. This study aimed to examine the simultaneous effect of parental emotional validation and social support on the mental resilience of vocational high school students from intact families. A quantitative correlational approach with an ex post facto design was employed. The participants were 66 students of UPTD SMKN Balanipa, Polewali Mandar Regency, West Sulawesi, selected through purposive sampling based on the criterion of living with both parents in one household. Data were collected using Likert-scale questionnaires measuring parental emotional validation, perceived social support, and mental resilience. The instruments met item validity criteria (r >= .30) and reliability criteria (Cronbach's alpha > .60). Data were analyzed using descriptive statistics and multiple linear regression after the classical assumption requirements were fulfilled. The findings showed that parental emotional validation did not have a significant partial effect on mental resilience. However, parental emotional validation and social support simultaneously had a significant effect on students' mental resilience, F(2, 63) = 3.792, p = .028, with R² = .107. These results indicate that mental resilience is not shaped by family emotional processes alone, but by the interaction between family-based validation and broader social support. The findings imply that school guidance and counseling services should involve both parents and school-based support systems to strengthen students' resilience. Future studies are recommended to include school climate, coping strategies, self-esteem, and peer support as additional predictors.